(untitled) (Journal of Nonlinear Modeling and Analysis, 2024)
This paper delves into an examination of the existence, uniqueness and controllability results concerning impulsive functional fuzzy nonlinear neutral integro-differential equations with non-local conditions. Additionally, we explore the fuzzy solution within the context of normal, convex, upper semi-continuous and compactly supported interval fuzzy numbers. Our findings are derived through the application of the Banach fixed point theorem. Also, we illustrate the result with an example.